Attitude and its associated factors among adults towards traditional eye medicine in Gondar City, Northwest Ethiopia : a cross-sectional study - Munaw, Minychil Bantihun; Anbesse, Dereje Hayilu; Assefa, Natnael Lakachew (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
This study is to assess attitude and its associated factors among adults towards traditional eye medicine in Gondar city, North West Ethiopia. Traditional medicines are commonly practiced in Africa. It is believed to be alternative health care used in the developing world. It is a more widely available and affordable alternative to pharmaceutical drugs. In Africa, about 13.2- 82.3% of the population utilizes traditional eye medicine. A community-based cross-sectional study was conducted on 600 study participants using a pre-tested structured questionnaire. Data analysis was performed using Statistical Package for Social Sciences (SPSS) version 20 computer software. Association and strength between the outcome variable and independent variables were determined using the odds ratio with a 95 % confidence interval. A total of 633 subjects were included in the study with a 95 % response rate. Of the total study subjects, 292 (48.7 %) (95% CI: 44.7-52.7%)) had a good attitude towards traditional eye medicine use. Variables like being male (AOR=2.00(95% CI: 1.23-2.68)), family history of traditional eye medicine use (AOR=3.31(95% CI: 2.01-5.47)), availability of traditional healer (AOR=1.81(95% CI: 1.12-2.95)) and absence of health insurance (AOR=1.63(95% CI: 1.14-2.55)) were variables significantly associated with good attitude towards traditional eye medicine use. The result of this study shows that attitude towards traditional eye medicine use for the treatment of eye disease was fairly good. It indicates that almost half of the study participants had a good attitude towards traditional eye medicine use. Community awareness programme through collaboration of the health ministry and traditional healers on traditional eye medicine use can help to promote the right perception and reduce the risk of complications.